Barbados : Staff Report for 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2013 Article IV consultation highlights Barbados' weak economic performance and high public debt. Foreign reserves are under pressure as fiscal and external imbalances widened in 2012 and further in 2013. Recognizing the need for urgent action, the authorities announced ambitious budget consolidation proposals in 2013 aimed at strengthening the fiscal position and arresting the slide in reserves. Recent fiscal measures, if fully implemented, should stabilize debt levels by 2016. However, downside risks are considerable, and failure to implement corrective policies could result in a disorderly adjustment process. Even with full implementation, fiscal financing pressures and external sector sustainability would remain challenging.